A GIS-Based Road-Mapping Network for Responding to Future Terrorist Activities in Colombo, Sri Lanka - Pinnawala Sangasumana; Marabage Upul Krishantha; Ratnayake R.M.K. (European Scientific Journal, ESJ, 2020)
The contemporary world has been moving to a new direction where anti-terrorist strategies are adopted intelligently to confront new challenges of global terrorism. Sri Lanka experienced a brutal terrorist attack again just recently after a decade of the total defeat of one of the dangerous terrorist organizations in the World, Liberation Tigers of Tamil Eelam (LTTE), in 2019. The LTTE demanded the Northern and Eastern provinces. Colombo had been a major vulnerable location and the LTTE had been frequently carrying out attacks against civilian targets, key politicians, government officials, military installations, as well as economic and commercial targets for about three decades. This paper therefore focuses on the applicability of GIS-based road-mapping analysisto respond to future terrorist activities based on the previous experience of terrorist attacks in Sri Lanka. Based on the methodology used in this study, 29 GN Divisions of Colombo DSD were selected as research sites and network, and hotspots analysis were then employed. Research results revealed that there were approximately 97 vulnerable locations at marginalized spaces. Distance from security installation to vulnerable location ranges from 0.8 km to 2.4 km. Average responding time to any adversary action varies from 3 to 5 minutes. Junctions within the 400 m to 500 m distance from all vulnerable locations in the study area were identified as suitable road blocking points. Six GNDs were identified as major potential areas for terrorist activities. Petta and its neighboring wards seem to be the most vulnerable locations for terrorist activities in the future. Based on the accurate information from particular areas, terrorist activities can be monitored and prevented by this risk and emergency management road network system.